2014
DOI: 10.1111/jphp.12307
|View full text |Cite
|
Sign up to set email alerts
|

Uliginosin B, a natural phloroglucinol derivative, presents a multimediated antinociceptive effect in mice

Abstract: These data confirm the contribution of monoaminergic neurotransmission as well as provide the first evidence of glutamatergic neurotransmission contribution to the uliginosin B effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Five compounds isolated from Brazilian Hypericum species were already evaluated for their antinociceptive activity (uliginosin B, benzopyran HP1, austrobrasilol A, austrobrasilol B, and isoaustrobrasilol B) [3,10,13]. Uliginosin B and benzopyran HP1 promote their effects mediated by the activation of glutamatergic and opioid receptors, and by an opioid-like mechanism, respectively [10][11][12][13]. It is relevant to evaluate the antinociceptive effect of denudatin A (1) and selancin A (2) because these compounds present some different chemical features in relation to the previously tested phloroglucinol derivatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Five compounds isolated from Brazilian Hypericum species were already evaluated for their antinociceptive activity (uliginosin B, benzopyran HP1, austrobrasilol A, austrobrasilol B, and isoaustrobrasilol B) [3,10,13]. Uliginosin B and benzopyran HP1 promote their effects mediated by the activation of glutamatergic and opioid receptors, and by an opioid-like mechanism, respectively [10][11][12][13]. It is relevant to evaluate the antinociceptive effect of denudatin A (1) and selancin A (2) because these compounds present some different chemical features in relation to the previously tested phloroglucinol derivatives.…”
mentioning
confidence: 99%
“…To exclude that the behavior in the hot plate would be due to a sedative, muscle relaxant, or hypotensive actions, the motor performance of the mice treated with denudatin A (1) and selancin A (2) was evaluated in the rotarod apparatus. The analysis of the results (two-way RM ANOVA) demonstrated a main effect of the treatment and exposition session as well interaction between factors when considering the number of falls (▶ Recently, studies have demonstrated the antinociceptive activity of the dimeric acylphloroglucinols austrobrasilol A, austrobrasilol B, isoaustrobrasilol B [3], and especially, uliginosin B (4) [11][12][13]. The mechanism of action of uliginosin B seems to be due to the neuronal monoamine reuptake inhibition [8] with consequent activation of dopaminergic receptors and indirect stimulation of the opioid system [11].…”
mentioning
confidence: 99%
“…Previous data showed that ULI (15 mg/kg, i.p.) produces antinociceptive effect in hot-plate test [ 3 , 5 , 6 ]. We now show that the pretreatment with DPCPX and ZM 241385, selective adenosine A 1 and A 2A receptor antagonists, respectively, completely prevented the antinociceptive effect of ULI in the mice hot-plate test.…”
Section: Discussionmentioning
confidence: 99%
“…Uliginosin B (ULI) is a dimeric acylphloroglucinol consisting of filicinic acid and phloroglucinol moieties, which occurs in Hypericum species native to South America [ 1 ]. This molecular pattern has been proposed as a prototype to develop analgesic and antidepressant drugs [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation